John Murtagh's general practice companion handbook - Murtagh, John (McGraw-Hill Education, 2015)
This is an A-Z portable handbook for GPs and students on the go! Murtagh's "General Practice Companion Handbook, 6/e" is a concise version of the larger volume. It has been completely updated in line with the changes in the parent text.